Diversity of Purse Seine Vessels at Pekalongan Archipelago Fisheries Port (PPN) Above 100 Gross Tonnage - Moch Ricky Dariansyah; Yopi Novita; Budhi Hascaryo Iskandar; Indra Jaya; Vita Rumanti Kuniawati (Institut Teknologi Sepuluh Nopember, 2023)
This research aims to determine the diversity of purse seine vessels based on gross tonnage measurements which was carried out from April 2023 to July 2023. This study collected sampling data on purse seine vessels in the Pekalongan PPN, both when the vessels were berthed, and collective data sourced from the authorities Archipelago Fishing Port (PPN) Pekalongan. In this formulation, it begins with identifying the dimensions of the ship, measuring the volume of the fish hold and interviewing a number of crew members who work on the ship. The aim of this research is to identify the main dimensions of ships and describe the operation of purse seine ships. with an average ship size of over 100 gross tonnages to 200 gross tonnages with a crew of 35 to 40 people.